S34I Project: Secure and Sustainable Supply of Raw Materials for EU Industry - Ana Teodoro (2025)
The Secure and Sustainable Supply of Raw Materials for EU Industry - S34I project is researching and innovating new data-driven methods to analyze Earth Observation (EO) data, supporting systematic mineral exploration and continuous monitoring of extraction, closure, and post-closure activities to increase European autonomy regarding raw materials (RM) resources, and to use EO not only for the management of technical and environmental issues for a green transition but also to support public awareness, mining's social acceptance, and better legislation. S34I uses data from satellites, airborne, unmanned aerial vehicles, ground-based sensors, underwater hyperspectral imaging and conventional in-situ techniques/methods and fieldwork. The S34I project is supporting the technical experiments and pilot validations/demonstrations for the six pilot use cases and at different phases of the mining life-cycle to address the challenges of the topic: Onshore exploration (Aramo in Spain); Shallow water exploration (Ria de Vigo in Spain); Extraction (Gummern in Austria); and Closure/post-closure (Lausitz in Germany, Aijala and Outokumpu in Finland). The S34I project involves 19 partners from 12 European countries. The project started in January 2023 and ends in June 2025. (c) 2025 by SCITEPRESS - Science and Technology Publications, Lda.